Homosexuality, health and humanity: Hlebotomy and biases Against gays - Chadwick Co Sy Su, Chadwick Co Sy Su; Anthony C Cenizal, Paul Martin; E Dumagay, Teresita (2015)
During the authors’ visit to hospital for a voluntary blood donation, one of them took notice of a problematic question in a survey that would determine whether one is fit to donate blood. This question was “Nakipagtalik ka na ba sa iyong kauri?” which, in English, translates to “Have you ever had sexual relations with your own kind?”